Adoption of AI-Generative Image Tools and Evolving Designer Roles in Indonesia's Advertising Practices - Febriany, Indira (ULTIMART Jurnal Komunikasi Visual, 2025)
This research investigates the adoption of AI-generative image tools in Indonesia’s advertising practices and how it influences the requirements of designers in the industry. Through qualitative interviews with creative professionals from different agency backgrounds and after analyzing them thematically, it is found that the tools are embraced for efficiency and conceptual diversity. AI generative image tools are not yet considered a replacement for human creative judgment. Particularly in producing emotionally resonant or detail-sensitive visuals. The study identifies shifting role expectations for designers, emphasizing adaptability, conceptual skill, and aesthetic sensibility. The findings highlight the nuanced integration of AI in creative workflows and the influence of clients and ethical considerations. Keywords: AI generative image; advertising; designer roles; creative industry